2016
DOI: 10.1186/s13048-016-0281-4
|View full text |Cite
|
Sign up to set email alerts
|

Synuclein-γ (SNCG) expression in ovarian cancer is associated with high-risk clinicopathologic disease

Abstract: BackgroundSynuclein gamma (SNCG) expression is associated with advanced disease and chemoresistance in multiple solid tumors. Our goal was to determine if SNCG protein expression in ovarian cancer was correlated with clinicopathologic variables and patient outcomes.MethodsTissue microarrays from primary tumors of 357 ovarian, fallopian tube, and primary peritoneal cancer patients, who underwent primary surgery at Roswell Park Cancer Institute between 1995 and 2007, were immunohistochemically stained for SNCG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…This could explain why members of the synuclein family are found in non-neural cells, where they are not involved in synaptic transmission. For instance, synuclein family members are upregulated in certain cancers: alpha-synuclein in melanoma 67 ; and gamma-synuclein in breast 68,69 , prostate 70 , bladder 71 , uterine 72 and ovarian 73 cancer. Since we postulate that alpha-synuclein’s normal nuclear DNA binding and DDR functions may be conserved amongst the other family members, it will be important to test whether the synucleins could also be participating in the DDR in these forms of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why members of the synuclein family are found in non-neural cells, where they are not involved in synaptic transmission. For instance, synuclein family members are upregulated in certain cancers: alpha-synuclein in melanoma 67 ; and gamma-synuclein in breast 68,69 , prostate 70 , bladder 71 , uterine 72 and ovarian 73 cancer. Since we postulate that alpha-synuclein’s normal nuclear DNA binding and DDR functions may be conserved amongst the other family members, it will be important to test whether the synucleins could also be participating in the DDR in these forms of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a growing number of reports have described the function of SNCG in tumors. Strohl et al have shown that high expression of SNCG is bound up with invasion and development in ovarian cancer 8 . In MCF7 breast cancer cells, SNCG is also overexpressed, activating extracellular signal‐regulated kinase pathways and disrupting intercellular connections, which leads to cell migration, so it may also be a predictive marker for breast cancer 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The synuclein protein family is a small, soluble proteome composed of synuclein‐α, synuclein‐β and synuclein‐γ (SNCG), originally found in brain tissue, peripheral nerve tissue, and retina, which is involved in neurodegenerative diseases and cancers 6 . In recent years, researchers have found that SNCG is highly expressed in breast cancer, 7 ovarian cancer, 8 and bladder cancer 9 . The role of SNCG in cancer progression has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Synuclein family members (α, β and γ) have been extensively studied since their discovery thirty years ago due to their involvement in human pathology, mainly Parkinson's disease and cancer [ 26 , 27 ]. Thus, synuclein-γ (SNCG) abnormal expression has been described in a wide range of human cancer such as endometrial [ 28 ], bladder [ 29 ], prostate [ 30 ], ovarian [ 31 ], gastric [ 32 ], liver [ 33 ], lung [ 34 ], colon [ 35 ], and breast [ 5 , 6 ]. In ovarian and breast carcinoma, hypomethylation of SNCG gene CpG island is responsible for aberrant SNCG expression.…”
Section: Discussionmentioning
confidence: 99%